Corrosion of aluminum alloy used as sacrificial anode for steel embedded concrete transmission tower in brackish mud - Yahya Z.; Rahman M.M.; Daud M. (Trans Tech Publications Ltd, 2023)
Aluminum corrosion; Anodes; Cathodic protection; Concretes; Corrosion; Morphology; Scanning electron microscopy; Seawater; Steel corrosion; Surface morphology; Zinc; Anti-friction; Efficiency test; Exposed to; Heat-treatable alloys; Sacrificial anodes; Sacrificial cathodic protections; Strengthening effect; Transmission tower; Aluminum alloys